Anaerobic degradation of phenanthrene by a sulfate‐reducing enrichment culture - Anne M. Himmelberg; Thomas Brüls; Zahra Farmani; Philip Weyrauch; Gabriele Barthel; Wolfgang Schrader; Rainer U. Meckenstock (Environmental Microbiology, 2018)
Summary Anaerobic degradation processes are very important to attenuate polycyclic aromatic hydrocarbons (PAHs) in saturated, anoxic sediments. However, PAHs are poorly degradable, leading to very slow microbial growth and thus resulting in only a few cultures that have been enriched and studied so far. Here, we report on a new phenanthrene‐degrading, sulfate‐reducing enrichment culture, TRIP1. Genome‐resolved metagenomics and strain specific cell counting with FISH and flow cytometry indicated that the culture is dominated by a microorganism belonging to the Desulfobacteraceae family (60% of the community) and sharing 93% 16S rRNA sequence similarity to the naphthalene‐degrading, sulfate‐reducing strain NaphS2. The anaerobic degradation pathway was studied by metabolite analyses and revealed phenanthroic acid as the major intermediate consistent with carboxylation as the initial activation reaction. Further reduced metabolites were indicative of a stepwise reduction of the ring system. We were able to measure the presumed second enzyme reaction in the pathway, phenanthroate‐CoA ligase, in crude cell extracts. The reaction was specific for 2‐phenanthroic acid and did not transform other isomers. The present study provides first insights into the anaerobic degradation pathways of three‐ringed PAHs. The biochemical strategy follows principles known from anaerobic naphthalene degradation, including carboxylation and reduction of the aromatic ring system.